Spatial Modeling of Seaweed (Kappaphycus alvarezii) Cultivation Suitability Using GIS in Tinangkung Waters, Central Sulawesi, Indonesia - Sri Sudewi; Maharaji U Labugis; Ahsan Mardjudo; Fadly. Y Tantu; Umar Alatas (Journal Omni-Akuatika, 2025)
Particularly in the waters of Tinangkung, Central Sulawesi, the management of seaweed through marine spatial planning and evidence-based site selection remains extremely limited. The objective of this study was to assess the suitability of the environment for Kappaphycus alvarezii cultivation based on spatial modeling using a Geographic Information System (GIS). Eight environmental parameters were tested, namely depth, temperature, salinity, brightness, current velocity, nutrients (nitrate and phosphate), pH, and dissolved oxygen (DO), which were integrated into GIS software using the weighted overlay method to produce a land suitability map. The results indicated that the area was divided into three suitability classes, namely highly suitable (S1) covering an area of ± 722.79 ha (31.8%), suitable (S2) covering an area of ± 1,616.72 ha (66.6%), and unsuitable (N) covering an area of ± 88.29 ha (3.6%). The central and southern zones of Tinangkung Bay are classified as highly suitable (S1) with stable water characteristics, high clarity, and optimal oxygen and salinity content. In contrast, coastal and estuarine areas are classified as less suitable (S2) due to the influence of land runoff, which alters salinity and pH. GIS-based modeling is effective in integrating environmental data to assist in a comprehensive mapping of marine aquaculture suitability. This study produced the first land suitability map for K. alvarezii aquaculture in Tinangkung waters, which can serve as a scientific basis for the formulation of marine spatial planning policies and sustainable seaweed aquaculture management in Central Sulawesi.